Agreement between the 2- and 3-step methods for identifying subtle menstrual disturbances - Noordhof, D. A.; Taylor, M. Y.; De Martin Topranin, V.; Engseth, T. P.; Sandbakk, Ø.; Osborne, J. O. (International Journal of Sports Physiology and Performance, 2024)
Recent methodological recommendations suggest the use of the "3-step method," consisting of calendar-based counting, urinary ovulation testing, and serum blood sampling, for the identification of subtle menstrual disturbances (SMDs). However, the use of the 3-step method is not always feasible, so a less demanding combination of calendar-based counting and urinary ovulation testing, that is, the 2-step method, may be a viable alternative.